Cost and cost-effectiveness of dolutegravir-based antiretroviral regimens: an economic evaluation of a clinical trial. (15th December 2021) - Jamieson, Lise; Serenata, Celicia; Makhubele, Lebogang; Sokhela, Simiso; Mashabane, Nkuli; Akpomiemie, Godspower; Johnson, Leigh F.; Venter, Willem D.F.; Meyer-Rath, Gesine
Abstract : Supplemental Digital Content is available in the text Abstract : Background: HIV programmes world-wide currently make decisions regarding new antiretroviral therapy (ART) regimens with less side-effects and higher resistance barriers, which may improve adherence and viral suppression. Economic evaluation helps inform these decisions. Methods: We conducted an economic evaluation of three ART regimens included in the ADVANCE trial from the provider's perspective: tenofovir alafenamide (TAF)/emtricitabine (FTC)+dolutegravir (DTG) and tenofovir disoproxil fumarate (TDF)/FTC+DTG, compared with TDF/FTC/efavirenz (EFV). We used top–down and bottom–up cost analysis with resource utilization based on trial data and adjusted to emulate routine care. We estimated the cost-effectiveness of each regimen as cost per person virally suppressed or retained and per life-year saved, at 48 and 96 weeks. Results: Though the DTG-based trial arms were 2% more costly than TDF/FTC/EFV, both had slightly lower cost-per-outcome ($9783 and $9929/patient virally suppressed for TDF/FTC+DTG and TAF/FTC+DTG, respectively) than TDF/FTC/EFV ($10 365). The trial cost per additional virally suppressed patient, compared with TDF/FTC/EFV, was lower in the TDF/FTC+DTG arm ($2967) compared with TAF/FTC+DTG ($3430). In routine care, cost per virally suppressed patient was estimated as similar between TDF/FTC+DTG ($426) and TDF/FTC/EFV ($424) but more costly under TAF/FTC+DTG. Similar results were seen in the cost per additional person retained across scenarios. When modelled over 20 years, TDF/FTC+DTG was more cost-effective than TAF/FTC+DTG ($10 341 vs $41 958/life-year saved). Conclusion: TDF/FTC+DTG had similar costs per outcome as TDF/FTC/EFV in the routine care scenario but TDF/FTC+DTG was more cost-effective when modelled over 20 years.